Medication adherence status among patients with neurological conditions and its association with quality of life - Junaid Farrukh, Muhammad (Saudi Pharm J, 2021)
BACKGROUND/AIM: Medication non-adherence may cause significant morbidity and mortality in patients with chronic diseases and may increase the economic burden on the healthcare system. The prevalence of neurological disorders is increasing in Malaysia; however, comprehensive data on medication adherence among Malaysian patients with these disorders is limited. This study was conducted to determine the association of medication non-adherence with quality of life in patients with neurological problems. METHODS: A cross-sectional survey was performed in 370 patients diagnosed with epilepsy, Parkinson’s disease, stroke and Alzheimer’s disease at Neurology clinic. Patients aged 18 years or older, without documented physical or psychiatric illness such as schizophrenia and major depression, were included. Patient-administered questionnaires, such as the Malaysian Medication Adherence Scale and Medication Possession Ratio were used to determine medication adherence. An established EQ-5D-3L questionnaire was used to determine quality of life. Data were analysed using descriptive and inferential analysis. RESULTS: The overall prevalence of medication non-adherence among patients with neurological disorders was 59.2%. Among these neuromedical diseases, 69.2% (n = 9/13) of Alzheimer’s disease, 66.7% (n = 98/147) of epilepsy, 62.1% (n = 36/58) of Parkinson’s disease and 48.7% (n = 74/152) of stroke patients were found non-adherent. There was a significant difference in EQ-5D index scores (p = 0.041) between adherent and non-adherent patients. CONCLUSION: A high prevalence of medication non-adherence was found among patients with neurological disorders. The rate of non-adherence varied among different neurological conditions. There was a significant difference in quality of life between adherent and non-adherent patients.